A randomised control study of partial liquid ventilation after airway lavage with exogenous surfactant in a meconium aspiration syndrome animal model. Issue 2 (1st March 2000) - Nakamura, Tomohiko; Matsuzawa, Shigeyuki; Sugiura, Masatoshi; Tamura, Masanori
Abstract : AIMS: To test the hypothesis that lavage with exogenous surfactant before partial liquid ventilation in meconium aspiration syndrome (MAS) would improve debris removal, and therefore the effectiveness of partial liquid ventilation. METHODS: 12 newborn piglets were randomised into 4 groups, partial liquid ventilation or gas ventilation, with and without surfactant lavage. Physiological and blood gas data were compared between groups by analysis of variance. RESULTS: Arterial oxygen pressure (PaO2 ) was improved in the group treated with surfactant lavage when compared with the group not receiving surfactant. PaO2 in the group receiving surfactant lavage followed by partial liquid ventilation was further improved when compared with the group treated with surfactant lavage followed by gas ventilation and the group receiving partial liquid ventilation alone. CONCLUSION: The effectiveness of partial liquid ventilation in MAS might be enhanced by pretreatment with exogenous surfactant bronchial lavage.